The Role of Local Traditions in Fostering Religious Pluralism in Indonesia - Hutabarat, Franklin (11th International Scholars Conference, 2024)
This paper explores the role of local traditions in fostering religious pluralism in Indonesia, a nation with a rich tapestry of faiths. The analysis highlights how shared experiences, social cohesion (gotong royong), and interfaith dialogue promoted by these traditions contribute to a harmonious society. Examples like Yadnya Kasada and Rewang festivals showcase this in action. The concept of syncretism, evident in practices like Toraja death rituals, further demonstrates peaceful coexistence. However, the paper acknowledges potential drawbacks. Local traditions may reinforce social hierarchies or create pressures to conform. Recognizing these limitations is crucial. Furthermore, government policies, education, and media play a significant role in supporting these traditions. Initiatives promoting interfaith dialogue, respect for diverse beliefs, and appreciation for local traditions can strengthen their impact. By learning from Indonesia’s experience, other diverse societies can develop strategies to foster religious pluralism. The paper concludes by recommending areas for further research and initiatives to strengthen the role of local traditions in Indonesia, promoting their continued relevance and impact.